Edukacja autorytarna : o przemocy symbolicznej w szkole - Helios, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The aim of this article is to reflect on education and the school system in the context of authoritarianism and symbolic violence. The subject reflection is based on two mental trails. The first shows that culture justifies symbolic violence at school. The second, however, treats symbolic violence in education as a manifestation of the school’s activity as a total institution.
Keywords: authoritarian education; symbolic violence; total institution; culture; Bourdieu, Pierre